Codebook-Based Hybrid Beamforming Using Combined Phase Shifters of High and Low Resolutions - Xu, Ke; Zheng, Fu-Chun; Xu, Hongguang; Zhu, Xu; Leung, Ka-Cheong (IEEE wireless communications letters, 2021)
The hybrid beamforming architecture where a combination of analog and digital precoders is employed has attracted much attention recently for its flexible trade-off between power consumption and performance. A codebook-based beamforming scheme is generally considered as a more practical solution rather than the adaptive beamforming schemes due to the large number of antennas. However, the constant amplitude constraint brought by the phase shifters (PSs) in the analog precoder always makes the codebook design problem a tricky and complicated one. In this work, we consider a novel combined PS (CPS) architecture where one high-resolution PS is connected to each RF chain in parallel with low-resolution PSs to each antenna. The corresponding codebook design aiming for ideal flat beam gains is then proposed for the CPS architecture. Simulation results reveal that the proposed scheme achieves a good trade-off between performance and energy efficiency compared with conventional single PS (SPS) and the recently proposed double PS (DPS) architecture.